2018
DOI: 10.1186/s13014-018-1190-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a real time group consensus peer review process in radiation oncology: an evaluation of effectiveness and feasibility

Abstract: BackgroundPeer review systems within radiation oncology are important to ensure quality radiation care. Several individualized methods for radiation oncology peer review have been described. However, despite the importance of peer review in radiation oncology barriers may exist to its effective implementation in practice. The purpose of this study was to quantify the rate of plan changes based on our group peer review process as well as the quantify amount of time and resources needed for this process.MethodsD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 18 publications
2
24
0
2
Order By: Relevance
“…Similarly to our proportion of cases peer reviewed, Albert et al [6] found 15 H&N cases (20.5%) from an overall of 73 cases presented resulting in one of the most frequently reviewed sites and also with one of the longest mean time of presentation (9 min).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Similarly to our proportion of cases peer reviewed, Albert et al [6] found 15 H&N cases (20.5%) from an overall of 73 cases presented resulting in one of the most frequently reviewed sites and also with one of the longest mean time of presentation (9 min).…”
Section: Discussionsupporting
confidence: 70%
“…Contouring corrections (53.8%) followed by dose/fractionation (26.9%) resulted in most frequent reason of change, similarly to data reported in other reviews [6,[12][13][14]16]. It is true that contouring plays an important role in our revision because it is known to be a major responsible for treatment outcomes and also isodose or DVH data are completely dependent on contour definition, especially when using IMRT-VMAT.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations